Improvement ability of male parent by gibberellic acid application to enhancing the outcrossing of cytoplasmic male sterility rice lines - Hassan HAMAD (University of Ljubljana, Biotechnical Faculty, 2021)
The study quantified the effect of gibberellic acid (GA3) as a pre-flowering treatment for male parent Giza 178 R and the influence of male to female ratio (2R:10A, 2R:12A, 2R:14A and 2R:16A) between male (R) to female (A) for two Cytoplasmic Male Sterility (CMS) lines (‘IR69625’ and ‘G46’) on hybrid rice seed production. The main plots were occupied by CMS lines while; GA3 application for male parent Giza 178R were arranged in the sub plots and male to female ratio was arranged in the sub-sub plots. The results indicated that, the, duration of floret opening, angle of floret opening, filaments exsertion, filaments length, anther length, plant height and number of tiller hill-1 of male parent Giza 178R were significantly at 300 g GA3 ha-1 concentration. Plant height, panicle exsertion, panicle length, flag leaf angle and 1000-grain mass of CMS were not significantly affected by the GA3 application for male parent and male to female ratio, while, number of fertile panicles hill-1, panicle mass, seed set, seed yield and harvest index of CMS lines were highly significantly affected. The highest seed yield (2.880 and 2.950 t ha-1) was obtained by CMS line IR69625A using 300 g GA3 ha-1 of male parent Giza 178R with male to female ratio of 2R:14A during both seasons.